Geometric and seabed parameter estimation using a vector sensor array - Experimental results from Makai experiment 2005 - Santos, P.; Joao, J.; Rodriguez, O. C.; Felisberto, P.; Jesus, S. M. (Oceans 2011 - Spain, 2011)
A vector sensor is constituted by one omni directional pressure sensor and three velocity-meters that are sensitive in a specific direction - x, y or z. Since a vector sensor is able to measure the three particle velocity directional components it acts as a spatial filter and therefore is advantageous in three dimensional direction of arrival (DOA) estimation. The potential gain obtained in DOA estimation can be extended to other geometric parameters such as source range and depth, as well as seabed parameters. The objective of this paper is to present experimental results of a four element vertical vector sensor array (VSA) data set collected during MakaiEx'05 experiment for geometric (range and depth) and seabed geoacoustic parameter estimation (sediment compressional speed, density and compressional attenuation). The parameter estimation problem is posed as an inversion method based on an extension of the conventional pressure only Bartlett estimator to particle velocity. The developed VSA based Bartlett estimator is proportional to the pressure only Bartlett estimator response by a directivity factor, providing an improved side lobe reduction or even suppression when compared with the pressure only response. This behavior will be illustrated for geometric and seabed parameters clearly showing the advantages of the use of VSA over hydrophone arrays. In source localization the VSA outperforms an array of hydrophones of same number of sensors. Moreover, when the VSA Bartlett estimator is applied for seabed parameter estimation, it will be shown that the estimation resolution of these parameters increased significantly, even for density and compressional attenuation, parameters difficult to estimate using an array of hydrophones.